On Nano Topological Spaces with Ideal Semi-p-open Sets - Ali, Shima H.; Esmaeel , R. B.; Radwan, Abdelaziz E. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
The purpose of this paper is to introduce a new type of spaces called nano topological spaces and investigate the relation between nano topological space and nano ideal semi preopen set. The objective of this study is to develop a nano topological model. We study this model from three aspects, which are lower, upper approximation and their properties. Basic properties and characterizations related to these sets are given. And define the concept Nano ideal semi preopen set by using nano topological space and some properties of this set. The main aim of rough sets is to increase the accuracy measure and reduce the boundary region of sets by increasing the lower approximations and decreasing the upper approximations.